Dietary Goji Shapes the Gut Microbiota to Prevent the Liver Injury Induced by Acute Alcohol Intake - Guo, Lin; Guan, Qijie; Duan, Wenhui; Ren, Yilin; Zhang, Xiao-Juan; Xu, Hong-Yu; Shi, Jin-Song; Wang, Fang-Zhou; Lu, Ran; Zhang, Hui-Ling; Xu, Zheng-Hong; Li, Huazhong; et al. (Frontiers in Nutrition, 2022)
Diet is a major driver of the structure and function of the gut microbiota, which influences the host physiology. Alcohol abuse can induce liver disease and gut microbiota dysbiosis. Here, we aim to elucidate whether the well-known traditional health food Goji berry targets gut microbiota to prevent liver injury induced by acute alcohol intake. The results showed that Goji supplementation for 14 days alleviated acute liver injury as indicated by lowering serum aspartate aminotransferase, alanine aminotransferase, pro-inflammatory cytokines, as well as lipopolysaccharide content in the liver tissue. Goji maintained the integrity of the epithelial barrier and increased the levels of butyric acid in cecum contents. Furthermore, we established the causal relationship between gut microbiota and liver protection effects of Goji with the help of antibiotics treatment and fecal microbiota transplantation (FMT) experiments. Both Goji and FMT-Goji increased glutathione (GSH) in the liver and selectively enriched the butyric acid-producing gut bacterium Akkermansia and Ruminococcaceae by using 16S rRNA gene sequencing. Metabolomics analysis of cecum samples revealed that Goji and its trained microbiota could regulate retinoyl β-glucuronide, vanillic acid, and increase the level of glutamate and pyroglutamic acid, which are involved in GSH metabolism. Our study highlights the communication among Goji, gut microbiota, and liver homeostasis.